Warming drives ecological community changes linked to host-associated microbiome dysbiosis - Greenspan, Sasha E.; Migliorini, Gustavo H. [UNESP]; Lyra, Mariana L. [UNESP]; Pontes, Mariana R.; Carvalho, Tamilie; Ribeiro, Luisa P.; Moura-Campos, Diego; Haddad, Celio F. B. [UNESP]; Toledo, Luis Felipe; Romero, Gustavo Q.; Becker, C. Guilherme (Nature Research, 2020)
Replicated bromeliad microecosystems were used to examine warming-induced community shifts and changes to tadpole gut microbiome. Tadpole growth was more strongly associated with cascading effects of warming on gut dysbiosis than with direct warming effects or indirect effects on food resources. Anthropogenic climate warming affects many biological systems, ranging in scale from microbiomes to biomes. In many animals, warming-related fitness depression appears more closely linked to changes in ecological community interactions than to direct thermal stress. This biotic community framework is commonly applied to warming studies at the scale of ecosystems but is rarely applied at the scale of microbiomes. Here, we used replicated bromeliad microecosystems to show warming effects on tadpole gut microbiome dysbiosis mediated through biotic community interactions. Warming shifted environmental bacteria and arthropod community composition, with linkages to changes in microbial recruitment that promoted dysbiosis and stunted tadpole growth. Tadpole growth was more strongly associated with cascading effects of warming on gut dysbiosis than with direct warming effects or indirect effects on food resources. These results suggest that assessing warming effects on animal health requires an ecological community perspective on microbiome structure and function.